Tissues Expression, Polymorphisms Identification of FcRn Gene and Its Relationship with Serum Classical Swine Fever Virus Antibody Level in Pigs - Liu Yang (Asian-Australasian Journal of Animal Sciences, 2012)
Neonatal Fc receptor (FcRn) gene encodes a receptor that binds the Fc region of monomeric immunoglobulin G (IgG) and is responsible for IgG transport and stabilization. In this report, the 8,900 bp porcine FcRn genomic DNA structure was identified and putative FcRn protein included 356 amino acids. Alignment and phylogenetic analysis of the porcine FcRn amino acid sequences with their homologies of other species showed high identity. Tissues expression of FcRn mRNA was detected by real time quantitative polymerase chain reaction (Q-PCR), the results revealed FcRn expressed widely in ten analyzed tissues. One single nucleotide polymorphism (SNP) (HQ026019:g.8526 C>T) in exon6 region of porcine FcRn gene was demonstrated by DNA sequencing analysis. A further analysis of SNP genotypes associated with serum Classical Swine Fever Virus antibody (anti-CSFV) concentration was performed in three pig populations including Large White, Landrace and Songliao Black pig (a Chinese indigenous breed). Our results of statistical analysis showed that the SNP had a highly significant association with the level of anti-CSFV antibody (At d 20; At d 35) in serum (p = 0.008; p = 0.0001). Investigation of expression and polymorphisms of the porcine FcRn gene will help us in further understanding the molecular basis of the antibody regulation pathway in the porcine immune response. All these results indicate that FcRn gene might be regarded as a molecular marker for genetic selection of anti-CSFV antibody level in pig disease resistance breeding programmes.